The pros and cons of common actin labeling tools for visualizing actin dynamics during Drosophila oogenesis. - Spracklen, A.J.; Fagan, T.N.; Lovander, K.E.; Tootle, T.L. (Developmental Biology, 2014)
Dynamic remodeling of the actin cytoskeleton is required for both development and tissue homeostasis. While fixed image analysis has provided significant insight into such events, a complete understanding of cytoskeletal dynamics requires live imaging. Numerous tools for the live imaging of actin have been generated by fusing the actin-binding domain from an actin-interacting protein to a fluorescent protein. Here we comparatively assess the utility of three such tools - Utrophin, Lifeact, and F-tractin - for characterizing the actin remodeling events occurring within the germline-derived nurse cells during Drosophila mid-oogenesis or follicle development. Specifically, we used the UAS/GAL4 system to express these tools at different levels and in different cells, and analyzed these tools for effects on fertility, alterations in the actin cytoskeleton, and ability to label filamentous actin (F-actin) structures by both fixed and live imaging. While both Utrophin and Lifeact robustly label F-actin structures within the Drosophila germline, when strongly expressed they cause sterility and severe actin defects including cortical actin breakdown resulting in multi-nucleate nurse cells, early F-actin filament and aggregate formation during stage 9 (S9), and disorganized parallel actin filament bundles during stage 10B (S10B). However, by using a weaker germline GAL4 driver in combination with a higher temperature, Utrophin can label F-actin with minimal defects. Additionally, strong Utrophin expression within the germline causes F-actin formation in the nurse cell nuclei and germinal vesicle during mid-oogenesis. Similarly, Lifeact expression results in nuclear F-actin only within the germinal vesicle. F-tractin expresses at a lower level than the other two labeling tools, but labels cytoplasmic F-actin structures well without causing sterility or striking actin defects. Together these studies reveal how critical it is to evaluate the utility of each actin labeling tool within the tissue and cell type of interest in order to identify the tool that represents the best compromise between acceptable labeling and minimal disruption of the phenomenon being observed. In this case, we find that F-tractin, and perhaps Utrophin, when Utrophin expression levels are optimized to label efficiently without causing actin defects, can be used to study F-actin dynamics within the Drosophila nurse cells.